Essential operations management - Hill, Alex, 1972- 4 0 16; 1940- , Hill, Terry; 5 (New York : Palgrave Macmillan, 2011)
From two highly respected authors in the field, Essential Operations Management provides a concise, student-friendly overview of operations management, striking a balance between coverage of the service and manufacturing industries that reflects current trends and supported by well-developed international case studies and learning features --
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Industrial management.;Production management. -- 20; 20; 2